Minority Faiths And Marginalized Believers: Religious Difference In Modern Prose Narratives - Ayu Larasati; Maulina Nabila (Politeknik Siber Cerdika Internasional, 2025)
This qualitative study examines narrative strategies in modern prose literature that represent religious minorities and marginalized believers across diverse geographical and cultural contexts. Analyzing 28 contemporary narratives published between 1980 and 2024, the study investigates how authors utilize focalization, characterization, temporal structures, symbolism, and linguistic strategies to depict minority religious experiences and challenge dominant discourses. The research employs close reading methodologies and thematic analysis to examine texts representing Christian, Muslim, Jewish, and other minority communities across Asia, the Middle East, Africa, Europe, and the Americas. Findings reveal that narratives predominantly employ internal focalization through minority characters to provide intimate access to religious consciousness while maintaining a critical sociopolitical perspective. Characterization strategies balance humanization through ordinariness with attention to religious particularity, resisting both exoticization and assimilation. Temporal structures favor linear narratives with historical framing that contextualize contemporary persecution, while fragmented, nonlinear approaches formally enact trauma. Rich symbolic systems, including spatial marginality, border liminality, embodiment, and natural world imagery, convey complex dimensions of minority experience. Linguistic strategies such as code-switching and the integration of religious vocabulary mark an authentic minority voice while educating readers. Beyond representing persecution, narratives extensively depict resistance strategies including clandestine religious practice, cultural production, educational transmission, strategic accommodation, and diaspora formation. The research contributes to the concept of